Networked control systems and wireless sensor networks: theories and applications. - Yang, Shuang-Hua; Cao, Yi (Taylor & Francis, 2008)
Abstract This special issue aims to provide innovative research work that has recently been carried out in networked control and wireless sensor networks, including both theoretical developments, experimental and/or application research. Wired and wireless networks have been used as a platform in the remote monitoring and control. The applications cover a wide range from natural monitoring to ambient awareness, from military to surveillance, and from industrial plants to domestic home environments. This preface first introduces the basic concepts of networked control and wireless sensor networks, then presents the challenges in these areas, and finally summarises the five papers included in the special issue.